Respuesta :
Step-by-step explanation:
let the number be X
by question,
or, X + 52 = 3X
or,. 52 = 3X - X
or,. 2X = 52
or,. X = 52/2
or X = 26
hence that original number is 26.
you can follow me for more help
Let the number be x
- 3 times the original number is equal to the original number x + 52.
Then , above statement becomes
x + 52 = 3x
Solving for x , we have the following
[tex]\large\green\implies \tt \large \: \: x \: + \: 52 \: = \: 3x[/tex]
[tex]\large\green\implies \tt \large \: \: 52 \: = \: 3x \: - x[/tex]
[tex]\large\green\implies \tt \large \: \: 52 \: = \: 2x[/tex]
[tex]\large\green\implies \tt \large \: \: \cancel\frac{52}{2} \: = \: x \\ [/tex]
[tex]\large\green\implies \tt \large \: \: 26 \: = \: x[/tex]
Hence , the number is 26.